Abnormal Expression of Connexin43 in Cardiac Injury Induced by S-Band and X-Band Microwave Exposure in Rats - Yue Yin; Xinping Xu; Yabing Gao; Juan Wang; Binwei Yao; Li Zhao; Haoyu Wang; Hui Wang; Ji Dong; Jing Zhang; Ruiyun Peng (Journal of Immunology Research)
Although the effects of microwave exposure on the heart have gradually become the focus of domestic and foreign scholars, the biological effects caused by different doses and different frequency bands of exposure are still unclear. In this study, we will investigate the damaging effect of S-band and X-band microwave composite exposure on cardiac structure and function, as well as the pathophysiological significance of Cx43 in cardiac conduction dysfunction after exposure. We used S- and X-band radiation sources with the average power density of 5 and 10 mW/cm2 to expose Wistar rats to single or composite exposure. At the 6th hour, on the 7th, 14th, and 28th days after exposure, ECG was used to detect the electrical conduction of the heart, and the myocardial enzyme was measured by the automatic biochemical analyzer. We selected the observation time points and groups with severe damage to observe the changes of myocardial structure and ultrastructure with an optical microscope and TEM; and to detect the expression and distribution of Cx43 by western blotting and immunohistochemistry. After exposure, the heart rate increased, the P wave amplitude decreased, and the R wave amplitude increased; the content of the myocardial enzyme in serum increased; the structure and ultrastructure of cardiac tissue were damaged. The damage was dose-dependent and frequency-dependent. The expression of Cx43 in myocardial tissue decreased, and distribution was abnormal. Taken together, these findings suggested that the mechanism of abnormal electrical conduction in the heart of rats by S- and X-band microwave exposure might be related to the decreased expression and disordered distribution of Cx43 after microwave exposure.